Case report: G1P0A0 33 weeks pregnant with Eclampsia - Thare Pratama Petisa; Agung Ikhssani (POLTEKKES KEMENKES PONTIANAK, 2022)
Eclampsia is the onset of convulsions in women with preeclampsia. Pre-eclampsia is a pregnancy disorder with high blood pressure and large amounts of protein in the urine or other organ dysfunction. Onset may be before, during, or after delivery. Most often occurs during the second half of pregnancy. Seizures manifest as a tonic-clonic type and usually last about a minute. Pre-eclampsia is diagnosed when repeated blood pressure measurements are greater than or equal to 140/90mmHg, and signs of organ dysfunction, including proteinuria, thrombocytopenia, renal insufficiency, impaired liver function, pulmonary edema, cerebral symptoms, or abdominal pain. Usually, pregnant women have hypertension and proteinuria before the onset of seizures (convulsions). Long-lasting (persistent) headache, blurred vision Photophobia (i.e., the bright light causes discomfort), Abdominal pain Either in the epigastric region (the middle part of the abdomen above the umbilicus or at the umbilicus) and the right upper quadrant of the stomach (below the right side) rib cage), mental status changes (confusion) is one of these symptoms may appear before or after the seizure occurs. This case report reports the patient Mrs. T G1P0A0 33 weeks pregnant, not yet inpartu with Eclampsia.